Justification of Cesarean section in fetal distress: Experience in a tertiary care military hospital in Bangladesh - Khanum, Shakila; Chowdhury, Liza (BIRDEM Medical Journal, 2019)
Background: The trend of Caesarean section (CS) carried out is rising worldwide. One of the most common indications of CS is fetal distress which is based on the cardiotocograph (CTG) recording, abnormal fetal heart rate pattern and meconium stained liquor. The aim of this study was to carry out an audit of CS performed due to fetal distress in a tertiary care military hospital with a view to justify the methods for diagnosis of fetal distress to fetal outcome. Methods: This cross-sectional observational study was carried out over a period of 1 year and 6 months (July 2013 to January 2015) in the Combined Military Hospital (CMH), Dhaka. All pregnant women at or beyond 37 weeks of gestation who underwent CS for fetal distress were included. Neonatal outcome were assessed based on APGAR score and neonatal intensive care admission. Results: Among the 260 (100%) women who underwent CS due to fetal distress, mean age was 27.8 ± 5.3 years. More than half (54.6%) of the women were primigravida. Majority (48%) of the patients presented with spontaneous onset of labor and in 43% cases labor was induced by medical methods. In the majority (40%) of the patients, fetal distress was diagnosed by seeing abnormal patterns in CTG. During CS, signs of fetal distress was found in the majority (64.6%) of the patients (meconium stained liquor 42.3%, cord abnormality 13.5% and placental abnormality 8.8%). APGAR score of the newborn babies was abnormal (<7) in the majority (60%) cases. More than half of the newborn babies required admission in neonatal intensive care unit for different diagnosis. There was only 4 (1.5%) cases of neonatal death. Conclusion: The rate of CS for fetal distress in this study was comparable to other study findings and within recommendation of WHO. The high rate of identifiable causes of fetal distress as well as neonatal outcome justifies doing CS in these cases. Birdem Med J 2020; 10(1): 60-63